The readers of Novyi Mir : coming to terms with the Stalinist past - Kozlov, Denis, 1973- (Harvard University Press, 2013)
In the "Thaw" following Stalin's death, probing conversations about the nation's violent past took place in the literary journal Novyi mir (New World). Readers' letters reveal that discussion of the Terror was central to intellectual and political life during the USSR's last decades. Denis Kozlov shows how minds change, even in a closed society.